MENINGKATKAN HASIL BELAJAR SISWA DENGAN PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN PKn DI KELAS VIII B SMP NEGERI 1 PAYANGAN - TRISNIA MAYANI, A.A. ISTRI (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThis study aimed to determine how to improve the result learn at subject of Civic Education with the use model the study of co-operative of type jigsaw at student of class of VIII B SMP negeri 1 Payangan. This research represent the classroom action research ( PTK) of performed within twice action cycle, where researcher as teacher in study execution. Every cycle consisted of by the planning, execution, observation / evaluate and reflection. This Subjects Research is student of class of VIII B SMP Negeri 1 Payangan of school year 2012 / 2013 with the student amount 39 people. Is technics of data collecting used by: ( 1) observation sheet; ( 2) test and non test; ( 3) enquette. The analysis of he data used in this study is to use qualitative descriptive and quantitative analysis. The result of this study indicated that applying model the study of co-operative of type jigsaw in study of Civic Education ( PKN) can improve the result learn student. This matter is visible in execution of cycle of I and cycle II. Is Make-Up of result learn the student horizontally - flatten the class at observation of early equal to 60,53 completely learn 46,90%. Experiencing of improvement flatten the class at cycle I of equal to 12,56% horizontally - flatten the class reach 73,1 with the percentage flatten 73,1% if seen by into PAP of inclusive of high category, completely learn 53% While at cycle II experience of the improvement as much 7% with the value flatten the class reach 80 with the percentage flatten - flatten equal to 80% if seen by into PAP stay in the high category completely learn 84,61%.Keyword : The Study of Co-Operative of Type Jigsaw and Result of Learning.